Which accessible clinical features and laboratory findings might predict methotrexate success in children with juvenile idiopathic arthritis in Bosnia and Herzegovina? - Adisa Čengić; Velma Selmanović; Sniježana Hasanbegović; Hamza Izeta; Lamija Zečević; Nejra Džananović (Medicinski glasnik, 2025)
Aim: To determine whether demographic data, clinical features, and laboratory variables at disease onset can predict the response to methotrexate in juvenile idiopathic arthritis (JIA) patients. Methods: A cohort of 143 newly diagnosed JIA patients initially treated with methotrexate was enrolled in this study. Demographic, clinical, and laboratory parameters were analysed using univariate and multivariate logistic regression to identify predictors of response to methotrexate. The variables included erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), platelets, IgA, IgG, the number of active joints and age at disease onset. Treatment response was assessed at six months, with patients classified as responders (those who achieved clinically inactive disease according to the American College of Rheumatology - ACR criteria) or non-responders. Results: Poor response to methotrexate was associated with the number of active joints (p=0.0001; OR=2.7), baseline levels of CRP (p=0.044; OR=1.138), IgA (p =0.004; OR=2.159), and platelet count (p=0.01; OR=1.05). IgG level (P=0.236) did not correlate with the treatment response. Conclusion: We identified widely available and clinically acceptable biomarkers that can be utilized as predictive indicators of response to methotrexate in JIA patients.
Keywords: chronic joint inflam-mation; response; treatment